MANAJEMEN STRATEGI BADAN USAHA MILIK DESA (BUMDESA) TUAH SEKATA DALAM MENINGKATKAN PENDAPATAN ASLI DESA PEMATANG TINGGI KABUPATEN PELALAWAN TAHUN 2022-2023 - Eriyanti, Tika; Pane, Rico Purnawandi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
One strategy to make it easier for villages to obtain sources of village income is for the government to make policies that have been mentioned in Law Number 6 of 2014 concerning Villages, which states that villages are advised to have a business entity that is useful for meeting community needs, especially basic needs, and the availability of village resources that have not been utilized, and the availability of human resources capable of managing business entities as assets driving the community's economy. With the existence of Village-Owned Enterprises (BUM Desa), the village is expected to be able to explore the potential of both natural and human resources within the village area which will later be used as a source of village income. This research uses the theory of strategic management according to Wheleen and Hunger (2003), with four indicators, namely observing the environment, strategy preparation, strategy implementation, and evaluation or monitoring. The research method used is descriptive research with a qualitative approach. The types of data are primary data and secondary data, primary data obtained directly from informants. While secondary data is supporting data or strengthening primary data. Data collection techniques are carried out by means of interviews and documentation. The results of this study indicate that the management strategy of the Tuah Sekata Village-Owned Enterprise (BUMDesa) in increasing Village Original Income has four business units, namely 1) The savings and loan unit 2) clean water procurement unit 3) sales of goods and services unit includes rental of billboards and rental of agricultural equipment 4) photocopy unit. Through the four theoretical indicators BUMDesa Tuah Sekata still faces challenges in optimizing resource management, which requires improvement in strategy formulation to overcome threats and take advantage of opportunities. However, it is not optimal in its implementation, there are still several obstacles, namely (1) lack of capital sources (2) There is bad credit from the savings and loan unit and the sales unit (3) There are unproductive business units). Keywords: Management Strategy, Village-Owned Enterprises, Village Original Income